Diseño e implementación de sistema de riego automatizado y controlado por una placa Arduino para la finca “La Lucia” - Cervantes Rodríguez, William R. (2016)
The author's aim was to create an automated irrigation control system based on an Arduino Mega, In "La Lucia" farm La Pita site - Canuto Parish - Chone Canton, place that allowed to identify the problem and to propose a possible solution. The automated irrigation control system has several hardware devices complemented with such control keyboard 4x3, 2x12 LCD where the user has access to the management of the irrigation device, improving the control of daily activities and processes carried out in the crops area. The planned execution of the control was worked on the computer method Free Hardware that was used for the development of the conceptualization processes, management and development in the implementation of irrigation control, where it was necessary to gather information, identify strategic sectors for the installation of irrigation controllers, doing tests of irrigation control in prototypes having as a result the right operation of the control. Finally a trial basis was set on the real field where the user verified, and the author showed its correct function, obtaining favorable results in the good control of water use in the crops at "La Lucia" farm.